(untitled) (Nigerian Journal of Technology, 2016)
In power systems, both active and reactive power demands are never steady. Due to sudden load changes, frequency fluctuation problems occur in an interconnected power system. The Load Frequency Control (LFC) reduces the frequency deviation and maintains dynamic performance of the system. Non-linearities have made most of the controllers employed for the LFC inefficient. In this paper, a fuzzy logic proportional integral (PI) controller is proposed to eliminate these setbacks with the conventional controllers. The results showed a reduction in settling time, percent overshoot and steady state error. http://dx.doi.org/10.4314/njt.v35i3.18